Multimodal imaging and adaptive optics in internal limiting membrane dystrophy. Issue 8 (17th August 2020) - Oli, Avadhesh; Balakrishnan, Divya
Abstract : An 18-year-old boy presented with a mild blurring of vision in both his eyes for the last 2 years. His best-corrected visual acuity was 20/60 in both the eyes with normal colour vision. Fundus evaluation showed exaggerated shiny reflex from the internal limiting membrane (ILM) with the wrinkled inner retinal surface at posterior pole. No vessel attenuation or retinal pigment epithelium changes were evident. Optical coherence tomography showed thickened ILM, which was appreciated in fundus photo also. The electrodiagnostic tests were normal, and the photoreceptors appeared normal in adaptive optics in the central macula at 2°–4° eccentricity. Among the very few reported cases of Muller cells sheen dystrophy, our patient was the probably the youngest and was picked up by a thoughtful ophthalmologist in detailed clinical examination. Adaptive optics in the case of ILM dystrophy is also not reported earlier.